Pengaruh Operating Capacity, Sales Growth dan Firm Size terhadap Financial Distress - Yohana Yohana; M. Hendri Yan Nyale (Universitas Batanghari, 2023)
The purpose of this study was to determine whether operating capacity, sales growth and firm size affect the occurrence of financial distress conditions. The object of the research was the textile sector companies listed on the Indonesia Stock Exchange in 2016 – 2021. The sampling technique used purposive sampling with a sample of 60 secondary data in the form of annual financial reports and other financial data information that was processed based on the criteria for the financial year period in on. Observation of research data was carried out in the period from June to July 2022 on the website www.idx.co.id. The results of research and descriptive statistical tests using the G-Score model show that operating capacity, sales growth and firm size simultaneously have a significant effect on the prediction of financial distress. However, partially from the independent variable test, the results showed that only the sales growth variable had a significant effect on the prediction of financial distress with a Sig value of 0.997 with a probability value below or less than Sig 0.05. While other research variables have no effect on the prediction of financial distress or Sig greater than 0.05.